The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/bcpt.13560
|View full text |Cite
|
Sign up to set email alerts
|

CYP2D6*10 polymorphism and the enantioselective O‐desmethylation of S‐(+)‐ and R‐(‐)‐venlafaxine in Japanese psychiatric patients

Abstract: According to previous studies, R‐(‐)‐venlafaxine (VEN) has higher enantioselectivity than S‐(+)‐VEN, and the plasma concentration of R‐(‐)‐VEN varies depending on CYP2D6 activity. Therefore, we examined the pharmacokinetic effects of CYP2D6*10 genotypes on the steady‐state concentrations of the enantiomers of VEN. The individuals were 71 Japanese depressed patients treated with racemic VEN. The concentrations of the enantiomers of VEN and O‐desmethylvenlafaxine (ODV) were measured. Polymerase chain reaction (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The discovered properties of the JNK inhibitor can be used to develop a fundamentally new approach to personification and increase the effectiveness of venlafaxine antidepressant therapy [7,8]. Based on the identified phenomena, JNK inactivation in liver cells can increase the level of drug transformation in low metabolizers (persons with low CYP2D6 expression, or in patients with liver diseases [3,4,6]) to the normal level (i.e. in extensive metabolizers of venlafaxine).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The discovered properties of the JNK inhibitor can be used to develop a fundamentally new approach to personification and increase the effectiveness of venlafaxine antidepressant therapy [7,8]. Based on the identified phenomena, JNK inactivation in liver cells can increase the level of drug transformation in low metabolizers (persons with low CYP2D6 expression, or in patients with liver diseases [3,4,6]) to the normal level (i.e. in extensive metabolizers of venlafaxine).…”
Section: Resultsmentioning
confidence: 99%
“…In 30 min, the venlafaxine (Aarti Industries) was added to the homogenate in a dose of 100 ng/ml and the cell suspension was incubated at 37°C in a TS-100 thermoshaker (Biosan). In 30 min, 1, 2, and 4 h, the content of the main venlafaxine metabolite O-desmethylvenlafaxine (O-DVLF) was evaluated [6,7]. The control was liver homogenate containing equivalent amounts of venlafaxine and solvent (DMSO, final concentration of 0.15%).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CYP2D6 is involved in the metabolism of 5-HT in the brain, which is linked to psychiatric disorders, as well as the synthesis of serotonin and dopamine [ 90 ]. Among these alleles, *10 is a mutation with a high allele frequency in Asian populations [ 91 ]. A study on patients with recurrent depression found that an SNP in CYP2D6 was associated with the efficacy of the antidepressant duloxetine [ 92 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the specific roles of individual signal transduction pathways in regulating the xenobioticmetabolizing function of cells competent in this regard are largely unknown. Simultaneously, uncovering the involvement and distinct roles of particular signaling molecules in the biotransformation of pharmacologically active substances can form the basis for the development of innovative approaches to personalized pharmacotherapy [7][8][9][10][11]. Therefore, it is pertinent to investigate the potential for controlling the intensity and nature of substance transformation within the body by regulating intracellular signal transduction in metabolizing cells and creating 'Targeted Regulators of Xenobiotic/Drug Metabolism' [7,12].…”
Section: Introductionmentioning
confidence: 99%